Evaluating Dispatch-Assisted CPR Using the CARES Registry. (4th March 2018) - Shah, Manali; Bartram, Cherie; Irwin, Kevin; Vellano, Kimberly; McNally, Bryan; Gallagher, Timothy; Swor, Robert
Abstract: Objectives: Dispatch-assisted cardiopulmonary resuscitation (DA-CPR) has been shown to improve cardiac arrest survival. Recent literature has proposed dispatch metrics for provision of this intervention. Our objectives are to: use the Cardiac Arrest Registry to Enhance Survival (CARES) to compare current practice to proposed DA-CPR guidelines; describe barriers to DA-CPR; and assess the association of DA-CPR with out-of-hospital cardiac arrest (OHCA) survival. Methods: We reviewed data from structured dispatch reviews of 911 OHCA calls from 1/1/14–12/31/15. Dispatch data including whether dispatch CPR instruction was given, and time intervals to CPR instruction and provision were linked with OHCA data elements from field cardiac arrest process and outcome data. Descriptive data on barriers to dispatch-caller instruction and measures of dispatcher performance were calculated. We compared outcome of patients who received bystander CPR prior to the 911 call (BCPR), after dispatcher CPR instructions (DA-CPR), and not until Emergency Medical Services (EMS) arrival (no BCPR). Results: We identified 3335 cases from 32 dispatch agencies in 9 states that had dispatch and outcome data. CPR was performed prior to the 911 call by a bystander in 496 (14.9%) cases. Of all calls where the dispatcher talked to a bystander, dispatchers recognized cardiac arrest in 82.9% cases (1514/1827), with 31.6% calls recognized in <60 seconds. DA-CPR instructions were initiated in most (1320/1514, 87.2%) cases, and cardiac compressions were initiated in 73.7% (973/1320). DA-CPR was performed < two minutes in 21.4% of cases. In a multivariable analysis, BCPR (CPR prior to EMS arrival without instructions given) was associated with significantly improved patient survival (OR = 1.49, 95% CI 1.09, 2.04), and DA-CPR a non-significant improvement in survival to discharge (OR = 1.19, 95% CI 0.91, 1.56). Conclusions: Temporal measures of dispatch performance were substantially below proposed national standards. In this population, OHCA was frequently recognized and DA-CPR performed but was not associated with a significant improvement in survival.